ANALISIS TERJEMAHAN KALIMAT YANG MEREPRESENTASIKAN TUTURAN KESANTUNAN POSITIF DALAM NOVEL THE HOST KARYA STEPHENIE MEYER DAN DAMPAKNYA PADA KUALITAS TERJEMAHAN - Chairunnisa Chairunnisa; Djatmika Djatmika; Tri Wiratno (Prasasti: Journal of Linguistics, 2016)
This research aims is to describe: (1) kinds of positive politeness markers in The Host novel, (2) translation techniques are used in the sentence that represent speech act of positive politeness in The Host novel, (3) the effects of the translation techniques which used by translators in sentences which represent politeness positive against the translation quality in terms of accuracy and acceptability.